Dramatic loss of Ube3A expression during aging of the mammalian cortex - Williams, Kate; Irwin, David A.; Jones, David G.; Murphy, Kathryn M. (Frontiers in Aging Neuroscience, 2010)
Neurobiological studies of aging are beginning to link functional changes with a loss of experience-dependent plasticity. In the visual system, age-related functional changes include decreases in visual acuity, orientation selectivity, motion perception, and ocular dominance plasticity. A recent paper has shown that Ube3A, an E3 ubiquitin ligase that is absent in Angelman's Syndrome, is required for experience-dependent plasticity during development of the visual cortex. Knocking out Ube3A during development leads to rigidity of ocular dominance plasticity that is strikingly similar to the reduced plasticity seen in older animals. Furthermore, ubiquitin ligases have been linked with age-related neurodegenerative disorders and longevity. Ubiquitin ligases selectively mark proteins for degradation, and a balance between synaptic proteins and their degradation is important for neural transmission and plasticity. This led us to ask whether normal aging is characterized by a loss of Ube3A in the cortex. We used Western blot analysis in order to quantify Ube3A expression across the life span of humans, macaque monkeys, and cats. We found that Ube3A expression declines across the lifespan in human, monkey, and cat cortex. The losses were substantial (50-80%) in all areas studied which includes V1, V3, V4, frontal, and auditory cortex. In addition, when compared with other synaptic proteins there was a selective loss of Ube3A in human cortex. The progressive loss of Ube3A expression during cortical aging is an important new finding. Furthermore, the selective loss of Ube3A in human cortex highlights a specific vulnerability in human brain aging that may signify a dramatic shift in cortical function and plasticity.